Transmembrane Peptides as Inhibitors of Protein-Protein Interactions: An Efficient Strategy to Target Cancer Cells? - Albrecht, Camille; Appert-Collin, Aline; Bagnard, Dominique; Blaise, Sébastien; Romier-Crouzet, Béatrice; Efremov, Roman G.; Sartelet, Hervé; Duca, Laurent; Maurice, Pascal; Bennasroune, Amar (Frontiers in Oncology, 2020)
Cellular functions are regulated by extracellular signals such as hormones, neurotransmitters, matrix ligands and other chemical or physical stimuli. Ligand binding on its transmembrane receptor induced cell signaling and the recruitment of several interacting partners to the plasma membrane. Nowadays, it is well established that the transmembrane domain is not only an anchor of these receptors to the membrane, but it also plays a key role in receptor dimerization and activation. Indeed, interactions between transmembrane helices are associated with specific biological activity of the proteins as cell migration, proliferation or differentiation. Overexpression or constitutive dimerization (due notably to mutations) of these transmembrane receptors are involved in several physiopathological contexts as cancers. The transmembrane domain of tyrosine kinase receptors as ErbB family proteins (implicated in several cancers as HER2 in breast cancer) or other receptors as Neuropilins has been described these last years as a target to inhibit their dimerization/activation using several strategies. In this review, we will focus on the strategy which consists in using peptides to disturb in a specific manner the interactions between transmembrane domains and the signaling pathways (induced by ligand binding) of these receptors involved in cancer. This approach can be extended to inhibit other transmembrane protein dimerization as neuraminidase-1 (the catalytic subunit of elastin receptor complex), Discoidin Domain Receptor 1 (a tyrosine kinase receptor activated by type I collagen) or G-protein coupled receptors which are involved in cancer processes.